A Peningkatan Keterampilan Abad 21 Peserta Didik Sekolah Dasar Melalui Metode Mind Mapping - Melody Mayang Cendana Melody (Universitas Sarjanawiyata Tamansiswa, 2023)
The 21st century learning is learning that is designed so that children are able to keep up with the latest developments in Science and Technology (IPTEK). Students are required to master four learning skills called 4C which include critical thinking and problem solving skills (critical thinking and problem solving), collaboration (ability to work well together), communication (ability to communicate), and creativity (creativity). From various references it is known that Mind Mapping is an effective learning method in mapping creative thoughts and then integrating and developing the working potential of the brain, both right brain and left brain so that students can improve 4C skills. The research was carried out based on the principles of qualitative research and was carried out in two schools; Pergiwatu Public Elementary School and Bantar Muhammadiyah Elementary School involving the Principal, one Class V teacher, and one student from each school as data sources. Data collection was carried out using observation techniques, interviews based on interview guides, and documentation. Data analysis was carried out in 4 stages from the Miles and Huberman model, namely, data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that the application of the mind mapping method in improving the 21st century skills of elementary school students has gone well. The management of the mind mapping method that is carried out invites students to think critically, find various solutions to problems that occur, work well together, communicate well, and increase creativity in various fields, especially the field of fine arts. In addition, the role of the Principal and the Classroom Teacher is very large as a motivator, the Principal and the Teacher have a role as an innovation in the development of learning media.